Living, Caring, Learning – Collaborating across borders to support a haemophilia patient with a rare complication - Githinji Cyrus (The Journal of Haemophilia Practice)
Cyrus, a haemophilia nurse in Kenya, reflects on his experience of treating a patient with a rare complication of haemophilia in a setting with limited access to treatment. The patient developed a debilitating abdominal pseudotumor following an inadequately treated traumatic bleed. After consulting with experts in other countries, surgery was deemed too great a risk. Initiating FVIII prophylaxis with the aim of shrinking the pseudotumour was identified as the most appropriate approach to treatment, however supply issues made it difficult to maintain a prophylactic regimen. When the pseudotumour continued to grow, posing a risk to adjacent organs, an international partnership enabled the initiation of emicizumab prophylaxis through a clinical trial. It was hoped that emicizumab would prevent further bleeding into the pseudotumour and allow it to shrink over time. The patient continued to experience breakthrough bleeding and was withdrawn from the trial after 2.5 years. By this time the supply of FVIII to Kenya through the through the WFH Humanitarian Aid Program had increased and the patient was able to resume FVIII prophylaxis. The pseudotumour is now stable and he continues to be cared for by the same nursing team. Reflecting on this case, Cyrus highlights the value of sharing expertise across borders and working in partnership to try to ensure the best treatment outcome for a patient with a rare complication in a resource-constrained setting. He also reflects on being compassionate in his practice and the importance of a holistic approach to patient support.